Monitoring Sistem Kontrol Mesin Drying Kopi Secara Real Time Berbasis IoT - Kusmiyati Kusmiyati; Arga Dwi Pambudi; Zaenal Arifin; Sari Ayu Wulandari; Muhammad Agus Purnomo; Kristoforus Ardian Setiadi; Nia Yunita Listianingrum (Elektrika, 2023)
The process of drying coffee beans often done by manually using sunlight which has its drawbacks, where coffee farmers cannot predict the weather which may rain at any time. If exposed to rain water, coffee beans that are slightly dry will become wet and moist again, which will affect the quality of the coffee beans. Therefore, in this research a literature study will be carried out, followed by the construction of an IoT-based coffee drying machine so that its condition can be monitored at any time. In the drying process, a PTC fan and heater will be used to regulate the temperature and humidity in the coffee drying machine to get better results in drying coffee. This research will also test how much temperature and humidity are optimal in the coffee drying machine, because it will also affect the drying time and the quality of the coffee produced. To determine the quality of the coffee beans and develop a coffee drying machine, researchers will collaborate with UKM Boyolali which has experience in drying coffee beans. IoT-based dying coffee machine has been made, with dimensions (80 x 47 x 115) cm, drying capacity of 30 grams, using electric fuel which is integrated with temperature and humidity sensors which function as drying temperature controllers, with measurement error calibration results of 1.2 and organoleptic tests show that the quality of the coffee produced by the tool/machine is better than the coffee produced by manual heating, where the coffee beans heated by the machine have a strong coffee aroma but do not smell burnt, the color is even, light brown in color and has a bitter taste and when crushed and dissolved there is no precipitate on the surface. The optimum temperature for the IoT-based dying coffee machine is 80ºC in 883 seconds or the equivalent of 15 minutes, which is equivalent to traditional drying by relying on sunlight for 10 days, while the optimal humidity for the IoT-based dying coffee machine is 15 %, this is in accordance with the quality standards of coffee as a result of heating.